Correlation Of Canine Parvo Virus Infection With Escherichia Coli In Clinical Cases - Kumar, Manesh; Raja, P.; Dixit, P.; Ingle, M.M.; Pawade, V. C.; Tembhurne, M.M.; P.A.; D. R, Kalorey (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Canine parvovirus (CPV) is a highly contagious and an acute life threatening infection that causes gastroenteritis, acute hemorrhagic diarrhoea, dehydration and immunosuppression resulting in morbidity and mortality in dogs (Appel et al., 1987). Long term excretion of CPV is major source of infection among dogs. E.Coli are considered as one of the major pathogens and found as natural commensals in gastrointestinal tract. Various diagnostic methods have been developed for detection of CPV from dog faeces (Manoj Kumar et al., 2011 and Cho et al., 2006) including Fastest Parvo Kit (Megacor Diagnostic, Astria ) and the same is being used in the present study for detection of CPV . Hence an attempt was made in the present study to explore the presence and association of E.Coli with Parvo virus in clinical dogs.